2003
DOI: 10.1590/s0004-28032003000400009
|View full text |Cite
|
Sign up to set email alerts
|

Growth assessment in children with extra-hepatic portal vein obstruction and portal hypertension

Abstract: Portal hypertension due to extra-hepatic portal vein obstruction was not associated with growth impairment in the group of children studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Umbilical sepsis is the most frequently implicated factor; in various studies, the history of sepsis is available in 0-56% of children with EHPVO [7]. We found that of 232 patients seen over 5 years, 47 had been delivered at home and 12 had history of umbilical sepsis [10].…”
Section: Discussionmentioning
confidence: 78%
“…Umbilical sepsis is the most frequently implicated factor; in various studies, the history of sepsis is available in 0-56% of children with EHPVO [7]. We found that of 232 patients seen over 5 years, 47 had been delivered at home and 12 had history of umbilical sepsis [10].…”
Section: Discussionmentioning
confidence: 78%
“…75 Another study however did not show any growth impairment in children with PVT. 76 Chronic PVT in adults presents with recurrent upper gastrointestinal bleed like children. Bleed may occur from esophago-gastric varices or ectopic varices in duodenum or elsewhere.…”
Section: Chronic Portal Vein Thrombosis (Extra Hepatic Portal Venous mentioning
confidence: 99%
“…83 An early report of marked growth retardation in children with extrahepatic portal vein obstruction 86 has not been confirmed in subsequent studies. 87 Obstructive jaundice is an uncommon complication. 88,89 It was detected in 8 of 121 children presenting over a 14-year period with cavernous transformation and regressed after surgical decompression.…”
Section: Hepatic Arterymentioning
confidence: 99%